2014
DOI: 10.1007/s13762-014-0695-8
|View full text |Cite
|
Sign up to set email alerts
|

Organic amendments: effects on cereals growth and cadmium remediation

Abstract: Cadmium (Cd) is one of the toxic metals that adversely affect plant growth. Organic amendments may not only enhance nutrient status of soil, but they may also form complexes with Cd and reduce its availability to plants. This experiment was conducted to determine whether organic amendments (compost and biogas slurry) could stabilize/extract Cd and alleviate the adverse effects of Cd on the growth of two cereals, wheat and maize. Organic amendments along with four varying levels of Cd (0, 5, 20, 50 mg kg -1 soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 32 publications
(34 reference statements)
3
15
0
Order By: Relevance
“…In addition, in this work, the application of the humic substances enhanced Cd remediation efficiency of A. wardii. The RF values in underground part of ME, which increased from 0.73 to 0.91 %, were apparently higher than those of NME and common crops, such as wheat and green bean (Prapagdee et al 2014;Ahmad et al 2015). These results indicated that ME possessed greater ability of root remediation with the increasing application of the humic substances.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…In addition, in this work, the application of the humic substances enhanced Cd remediation efficiency of A. wardii. The RF values in underground part of ME, which increased from 0.73 to 0.91 %, were apparently higher than those of NME and common crops, such as wheat and green bean (Prapagdee et al 2014;Ahmad et al 2015). These results indicated that ME possessed greater ability of root remediation with the increasing application of the humic substances.…”
Section: Discussionmentioning
confidence: 78%
“…Several types of organic amendments have effectively reduced metal bioavailability in amended soils and their uptake by plants. For instance, compost produced from fruit peels significantly (P ≤ 0.05) reduced Cd concentration in wheat and maize (Ahmad et al 2015). Horse-and sheepmanure compost reduced Cu and Zn concentrations in shoots of Brassica juncea and metal bioavailability of Cu and Zn in soil.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Hence it is important to restrict the leaching of this insecticide to prevent groundwater contamination. Organic amendments are known to improve soil structure and fertility by adding essential nutrients and increasing the microbial community in the soil (Ahmad et al 2015). Organic matter also plays an important role in the retention of pesticides in soil.…”
Section: Introductionmentioning
confidence: 99%